Community-Based Ecotourism Management Model Supporting Sustainable Tourism in Desa Batu Jongjong, Kecamatan Bahorok, Kabupaten Langkat - Muhammad Khadry; Christina Indriani Sianipar (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
The existence of ecotourism in Desa Batu Jongjong, Kecamatan Bahorok, can be an opportunity for the village community. However, the management of ecotourism, especially in Desa Batu Jongjong, Kabupaten Langkat, has not fully provided benefits in terms of economy, ecology, and socio-culture. The issues prompting this research include the lack of human resources in the tourism sector, unclear regulations, and management models for tourist attractions. This is evident from the limited active involvement of the community in tourism activities. The main goal of this study is to develop a community-based ecotourism management model. This research uses a qualitative method with descriptive analysis, SWOT matrix, and the formulation of IFAS, EFAS, and internal and external matrices. Data collection was carried out through interviews, surveys, and field observations, involving selected stakeholders as informants. The SWOT analysis shows that ecotourism management in Desa Batu Jongjong has a total internal factor score of 3.34 and an external factor score of 3.31, placing Desa Batu Jongjong in cell 1, which means it is very strong. In this position, strategies such as market penetration, market development, management, and product development can be applied. Therefore, the model to be implemented includes enhancing promotional content, establishing and strengthening ecotourism institutions, actively involving visitors in management, increasing community involvement, developing integrated tourism packages, improving facilities and infrastructure, creating new tourist attractions, and enhancing community empowerment. By implementing these strategic measures, community-based ecotourism management in Desa Batu Jongjong can be further optimized, supporting sustainable tourism, and providing significant economic, social, and environmental benefits for the local community.